Measuring the performance of 100 largest listed companies in Malaysia - Mohamad, N.; Said, F. (Academic Journals, 2010)
The purpose of this study is to measure and assess the performance of 100 largest listed companies in Malaysia. A modified strictly output-oriented Data Envelopment Analysis (DEA) model is used to measure the relative performance of each company by utilizing a list of normalized performance indicators based on data published in the Malaysian Business (16th October, 2009). The DEA scores indicate that only 6 and 19% of the companies are operating on the best-practice frontier under the assumptions of constant return to scale (CRS) and variable return to scale (VRS) respectively. No company exhibits increasing return to scale (IRS). Most of the relatively large (revenue-top-ranked) companies show serious scale inefficiency and exhibit decreasing return to scale (DRS). Ranking based on the performance index reveals that top-ranked companies by revenue are not necessarily top-ranked performers. Although ten of the seventeen governments linked companies, GLCs are top-20 by revenue, only one remains in the top-20 ranking by DEA. Three GLCs from bottom-20 by revenue join the top performers exhibiting full scale efficiency. Non-GLCs dominate 75% of the top-20 DEA ranking.